No deal! Sweden cancelled agreement with Elsevier to stand up for Open Science - Heyman Widmark, Cecilia; Hamrin, Göran (Septentrio Conference Series, 2019)
Watch the VIDEO. In this talk we highlight some results after the Swedish Bibsam consortium decided to cancel the agreement with scientific publisher Elsevier after 20 years as they couldn’t present a model that met the demands of the consortium. The requirements were immediate open access to all articles published in Elsevier journals by researchers affiliated to participating organisations as well as reading access to all articles in Elsevier’s journals. Bibsam also demanded a sustainable price model that enables a transition to open access publishing. We investigate the effects of this cancellation on Sweden’s largest technical university, the KTH Royal Institute of Technology. Method The study has two themes. First, we analyse the economics in earlier Bibsam-Elsevier agreements and what effects they have had for the budget and purchasing decisions made by the KTH Library. Second, we evaluate the response and the adapted behaviour of KTH researchers in the attempt to see if the cancellation has had severe negative effects for them. Results Our data collection gives an overview over the effects of the cancelled agreement at KTH. In particular, we observe how some of the money saved on the cancellation is used for individual article purchases and alternative services, thus lowering the effect of the cut-off. During our talk, we will also review some marketing strategies employed at KTH and Swedish libraries for making this cancellation process as smooth as possible. Limitations The short time period that has elapsed after the cancellation makes it difficult to see any long-time trends. The limited time frame also affects the validity of the researchers’ responses. Moreover, it is difficult to tell how the results from a case study from one university can be generalised to a global setting.